2017
DOI: 10.1016/j.imu.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small changes in medical and random-dot images comparing self-organizing map performance to human detection

Abstract: Radiologists use time-series of medical images to monitor the progression of a patient's conditions. They compare information gleaned from sequences of images to gain insight on progression or remission of the lesions, thus evaluating the progress of a patient's condition or response to therapy.Visual methods of determining differences between one series of images to another can be subjective or fail to detect very small differences. We propose the use of quantization errors obtained from selforganizing maps (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…In previous work (Wandeto et al, 2017a, Wandeto et al, 2017b, we have shown that the quantization error (QE) from SOM output after image learning can be effectively exploited for the fast and reliable detection of local changes in time series of medical images and satellite images for specific geographic regions of interest. The goal of the following proofof-concept study is to show that the QE varies consistently, reliably, and predictably with local variations in spatially distributed contrast signals in random-dot images and images with regularly distributed spatial contrast (geometric configuration).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work (Wandeto et al, 2017a, Wandeto et al, 2017b, we have shown that the quantization error (QE) from SOM output after image learning can be effectively exploited for the fast and reliable detection of local changes in time series of medical images and satellite images for specific geographic regions of interest. The goal of the following proofof-concept study is to show that the QE varies consistently, reliably, and predictably with local variations in spatially distributed contrast signals in random-dot images and images with regularly distributed spatial contrast (geometric configuration).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in our previous work [4], the quantization error (QE) of the output of image analysis analyses of satellite image contents for the corresponding region of interest, can be provided in the light of consistent variations in the QE. SOM analysis on time series of satellite images is fast (less than two minutes for a series of images), and represents a promising technique for the automatic tracking and harvesting of landscape information in large bodies of satellite images.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work [4] had shown that a specific output variable of the SOM, the quantization error (QE), can be exploited as a diagnostic indicator for the presence of potentially critical local changes in medical image contents. In the present work, to further highlight the potential of this new computational approach, we used the QE output from SOM analyses of satellite images of Las Vegas, generated across the years 1984-2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple functional architecture of the self-organizing map may be applied to the unsupervised classification of massive amounts of patient data from different disease entities ranging from inflammation to cancer, as shown recently [35]. Other recent work [102][103][104][105] has shown the quantization error (QE) in the output of a basic self-organized neural network map (SOM); in short, the SOM-QE is a parsimonious and highly reliable measure of the smallest local change in contrast or color data in random-dot, medical, satellite, and other potentially large image data. The SOM is easily implemented, learns the pixel structure of any target image in about two seconds by unsupervised "winner-take-all" learning, and detects local changes in contrast or color in a series of subsequent input images with a to-the-single-pixel precision, in less than two seconds for a set of 20 images [106,107].…”
Section: Som For Single-pixel Change Detection In Large Sets Of Imagementioning
confidence: 99%